ANALISIS FENOMENA FLYPAPER EFFECT PADA KINERJA KEUANGAN KOTA BENGKULU - Septriani Septriani; Armelly Armelly; Retno A Ekaputri; Esti Pasaribu (Department of Accounting, Faculty of Economics, Universitas Sriwijaya, 2020)
The purpose of this research is to know the possibility of flypaper effect on Financial Performance of Bengkulu City by knowing the influence of locally-generated revenue (PAD), General Allocation Fund (DAU) to Bengkulu City. This reaseach used the time series data about the Budget Realization Report (LRA) of Bengkulu City and the Financial Statistics of Bengkulu Province which provided by the Central Bureau of Statistics of Bengkulu Province. Data analysis tool used is multiple regression analysis.The empirical results of this research shows that the first, PAD has influential positive and significant to regional expenditure against the Bengkulu City, DAU has influential positive and significant regional expenditure against the Bengkulu City. The second, flypaper effect phenomenon is not occurring on financial performance of the Bengkulu City, it is seen of the value of the coefficients PAD greater than the value of the coefficients general allocation fund (DAU) and the result is significant on ? = 0.05.